1977
DOI: 10.1159/000240996
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Neonatal Plethora

Abstract: Blood volume and clinical data are reported on 8 premature and 3 full-term infants who presented with symptoms apparently due to polycythemia or hypervolemia. These cases termed ‘symptomatic neonatal plethora’ were caused by large placental transfusions associated with delayed clamping of the umbilical cord. Tachypnea, mild cyanosis, plethoric skin color, and neurological depression persisted on average for 30 h after birth. Chest X-rays showed mild cardiomegaly, pulmonary congestion and edema, and pleural eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 23 publications
(28 reference statements)
1
34
1
2
Order By: Relevance
“…Other risks of DCC are transient tachypnea 10 , symptomatic polycythaemia 11 , increased blood viscosity 12 and hyperbilirubinaemia 13 of the term infant. However no clinically significant adverse effects consequent to these changes have been demonstrated by well-designed studies.…”
Section: Research Articlementioning
confidence: 99%
“…Other risks of DCC are transient tachypnea 10 , symptomatic polycythaemia 11 , increased blood viscosity 12 and hyperbilirubinaemia 13 of the term infant. However no clinically significant adverse effects consequent to these changes have been demonstrated by well-designed studies.…”
Section: Research Articlementioning
confidence: 99%
“…We noted no neonatal polycythemia in the appropriate for gestational age preterm group. It appears that preterm infants do not rapidly extravasate sufficient plasma out of their circulation to produce significantly elevated Hct values [16].…”
Section: Discussionmentioning
confidence: 94%
“…Later in the neonatal life, a venous Hct equal or higher than 65% is considered as neonatal polycythemia. Polycythemia and secondary hyperviscosity have been associ ated with various life-threatening conditions, including cardiopulmonary [6][7][8], renal [9], neurologic [10][11][12], and other associated dis turbances [13][14][15], However, little is reported about neonatal polycythemia in the preterm infant [16,17], We conducted this study in order to establish whether or not a relation ship exists between umbilical cord venous Hct at birth and the value 2 h later in both preterm and full-term newborn infants. We also attempted to determine whether there is a relationship between both Hcts and gesta tional age, reticulocyte count, total blood sol utes, and blood pH at birth.…”
Section: Introductionmentioning
confidence: 99%
“…First, the authors' review of the literature is incomplete. There is only one actual report of a study relating cord clamping and symptomatic polycythemia [2] from 1977. We have found that the older study lacks the methodological rigor expected today and was not a randomized controlled trial (RCT).…”
Section: Dear Sirmentioning
confidence: 99%